Peningkatan Pengetahuan tentang Pembangunan Berkelanjutan Menggunakan Media Cerita Bergambar di Tingkat Sekolah Dasar - Yoga Suharman; Sadewa Purba Sejati; Dimas Adi Pratama (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
This community service entitled Enhancement Knowledge of Sustainable Development with Pictorial Story at Elementary School was carried out to strengthen the knowledge capacity and attitude related to groundwater resources in Bronggang Baru, Cangkringan District, Sleman, Yogyakarta. The method of implementing community service was conducted by three steps, consist of 1) literature review and problem analysis, 2) interviews and analysis of partner needs, and 3) developing and delivering the media of pictorial story about sustainable development and its relation to groundwater. The result of the activity shows that 80% of the total 25 Siswa/i s who attended knew more about the insights of sustainable development, particularly regarding geographical conditions and water resources of local area.